2014
DOI: 10.1371/journal.pone.0114918
|View full text |Cite
|
Sign up to set email alerts
|

MTO1-Deficient Mouse Model Mirrors the Human Phenotype Showing Complex I Defect and Cardiomyopathy

Abstract: Recently, mutations in the mitochondrial translation optimization factor 1 gene (MTO1) were identified as causative in children with hypertrophic cardiomyopathy, lactic acidosis and respiratory chain defect. Here, we describe an MTO1-deficient mouse model generated by gene trap mutagenesis that mirrors the human phenotype remarkably well. As in patients, the most prominent signs and symptoms were cardiovascular and included bradycardia and cardiomyopathy. In addition, the mutant mice showed a marked worsening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…The increased sensitivity of cardiac tissue as a consequence of a perturbed mitochondrial translation has recently been recapitulated in an MTO1 mouse model. 43,44 It is possible that the higher degree of mt-tRNA hypomodification detected in individual 65205 ( Figure 4 ) and the consequent impairment of mitochondrial translation accounts for the more severe symptoms in this case ( Table 1 ). The latter is also supported by a modestly lowered respiration rate in the 65205 fibroblast ( Figure S6 ), but no detectable changes in oxygen consumption in the 73901 fibroblast.…”
Section: Main Textmentioning
confidence: 95%
“…The increased sensitivity of cardiac tissue as a consequence of a perturbed mitochondrial translation has recently been recapitulated in an MTO1 mouse model. 43,44 It is possible that the higher degree of mt-tRNA hypomodification detected in individual 65205 ( Figure 4 ) and the consequent impairment of mitochondrial translation accounts for the more severe symptoms in this case ( Table 1 ). The latter is also supported by a modestly lowered respiration rate in the 65205 fibroblast ( Figure S6 ), but no detectable changes in oxygen consumption in the 73901 fibroblast.…”
Section: Main Textmentioning
confidence: 95%
“…Early linkage analyses and recent genome-wide association studies with exome sequencing revealed pathogenic mutations in mt-tRNA-modifying enzymes associated with specific disorders; PUS1 in mitochondrial myopathy and sideroblastic anemia 29 ; MTU1 in acute infantile liver failure 30 33 ; GTPBP3 in hypertrophic cardiomyopathy, lactic acidosis, and encephalopathy or Leigh syndrome 34 , 35 ; MTO1 in hypertrophic cardiomyopathy and lactic acidosis 36 38 ; TRIT1 in encephalopathy and myoclonic epilepsy 39 ; and NSUN3 in combined mitochondrial respiratory chain complex deficiency 27 . Genetic studies with mouse models revealed the significant roles of Cdk5rap1 in OXPHOS deficiency and cardiomyopathy 40 , Mto1 in cardiomyocytes 41 , 42 , and Mtu1 in liver failure 43 .…”
Section: Introductionmentioning
confidence: 99%
“…The high degree of similarity of clinical phenotypes between patients with GTPBP3 and MTO1 mutations, an uncharacteristic attribute of mitochondrial disease causing genes, corroborates the notion that these two enzymes act in tandem. The phenotype of an MTO1-deficient mouse model is found to accurately reflect that of the above patients (Becker et al 2014 ), the severity of which is found to be ameliorated by a ketogenic diet (Tischner et al 2015 ). Additionally, both GTPBP3 and MTO1 have been identified through linkage analysis as modifier genes in non-syndromic deafness caused by a m.1555A > G mutation in 12S mt-rRNA (Bykhovskaya et al 2004b ).…”
Section: Human Diseases Associated With Defects Of Mitochondrial Rna mentioning
confidence: 99%